Microwave-assisted synthesis of ZnO micro-javelins - Kelly, John; Chullanayil Padmanabhan, Sibu (My University, 2009)
The microwave (MW)-assisted formation of ZnO micro-javelins from zinc nitrate and urea in aqueous solution is described. The particles (named as `micro-javelins? because of their high aspect ratio and needle-like tips) grow hexagonally with well-defined facets in the ?01[1 with combining macron]0? direction and pointed tips in (0001) direction. Powder X-ray diffraction patterns show the appearance of a strikingly dominant (1000) orientation. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) investigations reveal the morphological evolution of these hexagonal ZnO particles with time. The effect of precursor concentrations, counterion type and MW irradiation power and their consequent influence on pH and Zn2+ ion concentration are investigated. A mechanism for the formation of the micro-javelins is postulated. The microwave induced supersaturation of Zn(OH)+ species under the weakly basic pH condition and the initial growth through the (000[1 with combining macron]) direction (oxygen-rich face) are proposed to be the key factors that dictate the formation of these ZnO micro-javelins. The present one-step microwave process is a straightforward and a reproducible method for the bulk synthesis of defect-free ZnO micro-javelins, which would find potential applications in microelectronic devices (e.g. lasers, cantilevers in surface probing equipment, etc.).
PUBLISHED
Keywords: micro-javelins; micro-javelins; Nanoscience & Materials